Analisis Outsourching Untuk Meningkatkan Daya Saing PT. Waskita Karya (Persero) - Anang Sunardi; Mohammad Yani; Dessica Dwiyuliana; Ernawati Mursalim; Renie Dwi Sulistyani; Hamka Hamka (Ekonomis: Journal of Economics and Business, 2022)
The fundamental goal of this exploration is to break down outsourcing and company competitiveness. A large number of literature reviews have been completed to accomplish the targets of this study. Outsourcing has become unavoidable and almost many multinational companies outsource to take advantage of scarce internal resources. In this study it was observed that the proprietor of the organization is the main winner in the outsourcing and off shoring situation. Furthermore, a detailed literature review shows that along with many other motives, the cost factor causes a major influence in outsourcing. Meanwhile, competitiveness is the company's ability to compete with commodities that meet customer needs in terms of price, quality and variety. This is possible as long as the company has a competitive advantage and its affirmation comes from the company's internal conditions and in a competitive and supportive economic environment.